HEAT-INTEGRATION RETROFIT STUDY OF A PETROLEUM REFINERY - DINCER, S; SENTARLI, I (ELSEVIER SCI LTD, 1991)
The operation of a petroleum refinery at TUPRAS, Tutunciftlik was assessed using the pinch-design method. By making use of heat integration in the heat-exchange network, appreciable amounts of energy can be saved as a result of a capital investment having a pay-back period of about 6.5 months.
Keywords: AVAILABLE ENERGY ANALYSIS; EXCHANGER NETWORKS; Energy & Fuels; Engineering